Black Power Movement as Depicted in Blakkasman (2018) Movie - Muhammad Faruq Bukhori; Arido Laksono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
America is a pluralistic country that often faces issues of racism and discrimination. This issue is often faced by African-Americans as one of the ethnic minorities. In this undergraduate thesis, I would like to analyze the Black Power Movement as depicted in the Blackkklansman movie using the sociology of literature approach by Abrams. Moreover, I also use an exponential approach to analyze the intrinsic elements in the movie. The result of the analysis shows that the Black Power movement occurs due to the white supremacy acts from the Ku Klux Klan members towards Blacks. As the result, the black community fought back by moving the masses of black people to carry out a revolutionary movement.Keywords: Blackkklansman; black  power; discrimination; Ku Klux Klan; revolutionary movement